Villous adenomas and carcinoma of the duodenum in Gardner's syndrome. Issue 757 (November 1988) - Sinha, J.; Williamson, R. C.
Abstract : Patients with Gardner's syndrome are increasingly found to have polyps on routine upper gastrointestinal endoscopy, and their risk of developing periampullary carcinoma is between 3-12%. We report a 45 year old man with Gardner's syndrome who presented with periampullary carcinoma 5 years after colectomy. Review of the literature amassed another 21 cases of periampullary carcinoma in patients with Gardner's syndrome.